2010
DOI: 10.1080/07315724.2010.10719883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muscadine Grape Seed Supplementation on Vascular Function in Subjects with or at Risk for Cardiovascular Disease: A Randomized Crossover Trial

Abstract: Background Muscadine grape seeds have high concentrations of polyphenolic compounds with antioxidant and other properties that would be expected to have favorable effects on endothelial function. Objectives To evaluate the effect of muscadine grape seed supplementation on endothelial function and cardiovascular risk factors in subjects with increased cardiovascular risk. Design In a randomized, double-blind, placebo-controlled crossover trial, 50 adults with coronary disease or ≥1 cardiac risk factor recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 33 publications
0
110
2
Order By: Relevance
“…45 In this double-blind, randomized crossover trial, there was no evidence that 4 weeks of daily supplementation with muscadine grape seed improved endothelial function measured by brachial flow-mediated dilatation (FMD). However, there was clear evidence that this supplement produced an increase in resting brachial diameter.…”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 94%
“…45 In this double-blind, randomized crossover trial, there was no evidence that 4 weeks of daily supplementation with muscadine grape seed improved endothelial function measured by brachial flow-mediated dilatation (FMD). However, there was clear evidence that this supplement produced an increase in resting brachial diameter.…”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 94%
“…Dietary interventions were grouped according to different categories, specifically vegetables (Table 1 ) [26-31], fruits (Table 2 ) [32-54], grape seeds (Table 3 ) [55-59], herbs (Table 4 ) [60-65], green tea (Table 5 ) [66-70], spices (Table 6 ) [71-78], beverages with mixed composition (Table 7 ) [8, 79-82] extracts with mixed composition (Table 8 ) [83-93] and cocoa products (Table 9 ) [66, 94-97]. Selection of the plant foods was performed on the basis of available human data on both oxidative and inflammatory markers: for example, raspberry, blackberry and olives were not included due to the lack of combined information.…”
Section: Overview Of Identified Studiesmentioning
confidence: 99%
“…Indeed, although improvements in FMD have been observed in hypercholesterolemic individuals after pure anthocyanin (320 mg) ingestion (3) and in healthy individuals and individuals with the metabolic syndrome or coronary heart disease after the intake of grape polyphenols (12)(13)(14), other studies with grape or grape extracts showed no significant vascular impact (15,16). Datasets on blood pressure have also been mixed, with blueberry intake decreasing blood pressure in individuals with the metabolic syndrome (17) but not in chronic smokers (18) or obese insulin-resistant individuals (19).…”
Section: Introductionmentioning
confidence: 99%